Christianisme et pédagogie. Les aspects méthodologiques choisis - Magier, Piotr (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article is metatheoretical, analytical and reporting. It shows the relationship between Christianity and pedagogy. The author analyses selected methodological problems that arise as a result of using the content of Judeo-Christian Revelation in pedagogy. Issues related to the possibility (legitimacy) of introducing religious knowledge into the structure of pedagogical theory, its functions and scope are discussed in the article. The text consists of three parts referring to: historical development of views on the relationship of religion (Christianity) to science; main methodological problems generated by using religious knowledge in the area of science (including the humanities) and the function of Christian Revelation in the field of pedagogy.